Synecdoche as a Lingua-Poetic Device in English and Uzbek Literature: A Comparative Study - M.A. Abdullaev (Indonesian Journal Publisher, 2026)
This article examines the lingua-poetic functions of synecdoche in English and Uzbek literary discourse from a comparative perspective. As a figure of speech grounded in the semantic relation between part and whole, synecdoche performs not merely a decorative role but also an interpretive and structural one within literary language. It condenses meaning, intensifies imagery, and transforms concrete lexical units into carriers of broader psychological, social, and philosophical significance. The analysis demonstrates that in English literature synecdoche frequently serves to heighten dramatic tension, philosophical generalization, and perceptual focus, whereas in Uzbek literature it more often articulates collective emotion, social atmosphere, and culturally embedded patterns of figurative thinking. Through the close analysis of selected literary passages from English and Uzbek literary traditions, the study demonstrates that synecdoche functions as a significant mechanism of semantic compression and aesthetic expansion in both traditions.